Roles of Marketing Innovation Strategies for Company Performance: A Systematic Literature Review Investigation - Sri Mulyono (Fundamental and Applied Management Journal, 2026)
Marketing innovation strategies are increasingly recognized as critical drivers of company performance. However, many firms fail to effectively align these strategies with their performance objectives, leading to inefficiencies and reduced competitiveness. This study aims to examine the role of marketing innovation strategies in enhancing company performance across different contexts. To achieve this objective, a systematic literature review (SLR) was conducted using the PRISMA approach, analyzing articles published between 2019 and 2024 and indexed in the Scopus database, focusing on marketing innovation, market strategies, and the roles of marketing innovation strategy. The findings reveal that marketing innovation has a direct and positive impact on company performance by enhancing customer value, strengthening customer loyalty, improving financial outcomes, and supporting sector-specific competitiveness in industries such as Islamic banking. In addition, marketing innovation is closely linked to product innovation, and their integration leads to stronger performance outcomes. The results also indicate that external innovation partnerships significantly strengthen marketing innovation strategies by providing access to additional resources and capabilities. Furthermore, the impact of innovation varies depending on firm size, with larger firms benefiting more from broader innovation approaches, whereas smaller firms tend to prioritize process-based innovations for immediate gains. This study concludes that marketing innovation strategies must be strategically aligned with organizational capabilities and contextual conditions to effectively improve company performance, offering important implications for managers and policymakers in developing more adaptive and integrated innovation strategies.